2013
DOI: 10.1186/cc12794
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all in severe infection: obesity alters outcome, susceptibility, treatment, and inflammatory response

Abstract: IntroductionObesity is an increasingly common comorbidity in critically ill patients. Whether obesity alters sepsis outcome, susceptibility, treatment, and response is not completely understood.MethodsWe conducted a retrospective analysis comparing three group of septic shock patients based on the intervals of actual body mass index (BMI) in patients enrolled in the VASST (Vasopressin and Septic Shock Trial) cohort. Primary outcome measurement was 28-day mortality. We tested for differences in patterns of infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 29 publications
6
123
1
6
Order By: Relevance
“…The group of patients with overweight and obesity are at a major risk of developing chronic diseases, such as systemic arterial hypertension and diabetes mellitus; however, in our study, less than 20% of the patients had a history of those clinical entities (15,28).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The group of patients with overweight and obesity are at a major risk of developing chronic diseases, such as systemic arterial hypertension and diabetes mellitus; however, in our study, less than 20% of the patients had a history of those clinical entities (15,28).…”
Section: Discussioncontrasting
confidence: 67%
“…However, in the context of critically ill oncologic patients with high BMI, the impact on mortality is unknown. Different reports have described that in patients with sepsis and septic shock, obesity is a protective factor against death (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [16][17][18][19] have indicated that the outcomes (ie, hospital mortality) and characteristics (ie, type of underlying infection) of critically ill obese patients differ from those of nonobese patients. These differences may be due to underlying pathophysiological mechanisms or differential use of therapies or suboptimal drug dosing.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, obesity does induce a chronic low-grade inflammatory state 38 and obese critically ill patients do have lower early levels of Interleukin-6 in sepsis. 39 Furthermore there is a tendency not to fully dose obese patients on a true mg/kg or mL/kg basis; as a result such obese patients may be 'relatively undertreated' which in other Table 5 Prognosis at collapse; discharged home or to rehabilitation. 29 intensive care spheres (eg, fluids, blood transfusion, vasopressors) have enhanced survival.…”
Section: Obesitymentioning
confidence: 99%